Life cycle of squall lines. Water and energy budgets - (:unkn) unknown (My University, 2009)
The African monsoon is a seasonal meteorological phenomenon providing about 90% of the annual precipitations over West Africa. Since a decrease in the intensity of the monsoon has been observed, an international multidisciplinary analysis of the African monsoon has been set up. Its major point was its intensive observation period during the Summer 2006. The elements of the monsoon providing most of the precipitations being the squall lines, this work documents water and energy budgets within those systems. The 27-29 July 2006 squall line is studied through mesoscale modelling using the Meso-NH model (Météo-France/CNRS). The sensitivity tests show that simulated fields and budgets are sensitive to the configuration and initial state of the model.
Keywords: African Research